Orbit and Formation Control for the Next Generation Gravity Mission*. Issue 17 (2016) - Colangelo, L.; Canuto, E.; Massotti, L.; Novara, C.; Lotufo, M.A.
Abstract: This paper focuses on the orbit and formation control for the Next Generation Gravity Mission (NGGM), under study at the European Space Agency. In our past study an innovative integrated orbit/formation model (IFC) has been designed, introducing a novel set of Hill-type equations. The aim of this study is the refinement and the enhancement of the IFC architecture. The proposed solution is based on a modified state predictor plus an extended hierarchical and multi-rate structure of the control law, with respect to the preliminary design. Care was taken in the control design to reduce as much as possible the demanded extra-thrust effort. This improved control strategy has been shown to be far less sensitive to the initial formation perturbations as well as capable of keeping the formation variables stable within the required band, all over the 10-year mission, through a low-thrust authority in the order of few milli-newtons.